Peningkatan Hasil Belajar Pengajaran Baca Tulis Alquran dengan Metode Peer Teaching di Kampung Persil Harapan Mulya Kelurahan Karya Mulya Kecamatan Kesambi Kota Cirebon - Wuriyanti, Wuriyanti; Fitriani, Nusantari; Prasetiyo, Hendrik Eko (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The Quran is a source of standard rules which guide Muslims in navigating the ark of life. The Koran functions as a filter so that humans do not fall into the valley of disgrace. When reading the Quran, the pronunciation must be clear and precise so that there are no wrong interpretations. Therefore, learning the Quran requires special methods, one of which is the peer teaching method. Apart from that, it also requires persistence and thoroughness, under the supervision of a teacher. Responding to this challenge, SMPIT Pesantren Qur'an Kayuwalang held a community service program teaching btq at 9 strategic locations, one of which was in Persil RW 06 Harapan Mulya village, Karya Mulya sub-district, Kesambi sub-district, Cirebon city. The program aims to eradicate Quran illiteracy. This research focuses on writing letters, pronouncing makhroj and tahsin. This research involved 12 students and 2 tutors using qualitative methods and approaches. With observation results ≥ 80% of students experienced a significant increase in learning outcomes. This is proven by the increase in posttest scores so it can be concluded that teaching reading and writing the Quran using the peer teaching method is able to increase student enthusiasm and learning outcomes.